The Behavioral Impact of Emotions in a Power to take Game: An Experimental Study - Ronald Bosman; Frans A.A.M. van Winden (Tinbergen Institute, 1999)
The power to take game is a simple two player game where players arerandomly divided into pairs consisting of a take authority and responder.Both players in each pair have earned an own income in an individual realeffort decision-making experiment preceding the take game. The gameconsists of two stages. In the first stage, the take authority decides howmuch income will be transferred from the responder to the take authorityafter the second stage (the so-called take rate). In the second stage, theresponder can punish the take authority by destroying own income. Thetransfer from the responder to the take authority will be based on theincome of the responder that is left after the second stage. In thisexperimental study, we are primarily interested in how emotions influenceresponder behavior. Our findings are the following. (1) A higher take ratesignificantly increases the intensity of irritation, contempt, and envy,and significantly decreases the intensity of joy and happiness. Sincenegative emotions are experienced as painful, there is direct hedonicimpact. (2) Irritation and contempt drive punishment behavior. (3) Thereare discontinuous “jumps” in the behavior of responders. They either chooseno punishment (destroy nothing) or the highest level of punishment (destroyeverything). (4) Expectations have a significant effect on the probabilityof punishment but not on the intensity of experienced emotion. We explainthis last result in terms of norm-related regulation of emotions.
Keywords: A12; C72; C91; C92; 330; emotions; punishment; expectations; social norms; experiment; Spieltheorie; Test; Theorie; Emotion